Zearalenone screening of human breast milk from the Naples area. Issue 1 (2nd January 2016) - Massart, Francesco; Micillo, Flora; Rivezzi, Gaetano; Perrone, Laura; Baggiani, Angelo; Miccoli, Mario; Meucci, Valentina
Abstract : The mycotoxin zearalenone exhibits estrogenic and anabolic properties in several animal species, humans included. Food contamination by zearalenone is caused either by direct contamination of grains, fruits, and their based-products or by "carry-over" of mycotoxins in animal tissues, milk, and eggs after intake of contaminated feedstuff. Now, a survey on zearalenone contamination in breast milk of healthy primiparous women living in the Naples countryside was conducted. From 47 healthy primiparous women, breast milk samples were collected within the first six weeks after delivery as well as clinical data of mother–newborn pairs. Breast milk analyses were performed with both competitive indirect enzyme-linked immunosorbent assay and high-performance liquid chromatography with fluorescence detection. At 36.9 ± 2.6 days after vaginal delivery, the mean zearalenone contents of the breast milk samples were 1.13 ± 0.34 µg/L. The zearalenone levels correlated with both mother weights before pregnancy ( r = −0.506; P < 0.001) and at delivery ( r = −0.351; P < 0.05). The present results indicate that breast milk may be contaminated with zearalenone.